RELATIONSHIP BETWEEN ATTITUDES LEARNING AND ACHIEVEMENT OF INTEREST LEARNING WITH LEARNING THE BASICS OF COST OF DISCUSSION AUTOMOTIVE AUTOMOTIVE DEPARTMENT OF CLASS X SMK PIRI SLEMAN EVEN SEMESTER OF STUDY 2013/2014 - Deril Gusa Wijaya; Isis Rachmadi (Universitas Sarjanawiyata Tamansiswa, 2014)
The purpose of the study is (1) determine whether there is a relationship between attitude and academic achievement of learning the basics of the subject of automotive grade students majoring in automotive x semester SMK PIRI SLEMAN; (2) to determine whether there is a relationship between interest in learning the subject learning achievement basics of automotive grade students majoring in automotive x SMK PIRI SLEMAN semester; (3) the attitude of learning and interest in learning the subject learning achievement basics of automotive grade students majoring in automotive x SMK PIRI SLEMAN second semester of the school year 2013/2014. The research hypothesis (1) There is a positive and significant relationship between attitude and academic achievement of learning the basics of the subject of automotive grade students majoring in automotive x SMK PIRI SLEMAN semester; (2) There is a positive and significant relationship between interest in learning the subject learning achievement basics of automotive grade students majoring in automotive x SMK PIRI SLEMAN semester; (3) There is a positive and significant relationship between learning attitude and interest in learning the subject learning achievement basics of automotive grade students majoring in automotive x SMK PIRI SLEMAN second semester of the school year 2013/2014. This research was conducted at SMK PIRI SLEMAN the second semester of academic year 2013/2014 population in this study were all students of class X automotive majors are numbered 105 students and this study using simple random sampling with Isaac and Michael computation techniques to obtain 2 as a sample. This research is correlational and ex post facto categorized. Data collection techniques with a questionnaire and a test of learning achievement. The validity of the items obtained from the product moment correlation. About the reliability obtained with the formula stated alpha and reliable. Before the data were analyzed first tested the prerequisite analysis of the normality test, linearity, and multicollinearity test. Analysis using partial correlation analysis and multiple regression analysis.Based on the analysis of the results obtained the following results: (1) There is a positive and significant relationship between the attitude of Learning (X1) with Achievement Automotive Basics (Y); (2) There is a positive and significant relationship between Interests Learning (X2) with Achievement Automotive Basics (Y); (3) There is a positive and significant relationship Attitude Study (X1) and Interest in Learning (X2) with Achievement Automotive Basics (Y).